Adverse childhood experiences and stimulant use disorders among adults in the United States. (May 2021) - Tang, Shichao; Jones, Christopher M.; Wisdom, April; Lin, Hsien-Chang; Bacon, Sarah; Houry, Debra
Highlights: Adverse childhood experiences (ACEs) were common among adults reporting stimulant use. Greater ACE exposure was associated with early onset of stimulant use. Number of ACEs was significantly associated with stimulant use and use disorder. Abstract: Recent data indicate a resurgence of stimulant use and harms in the United States; thus, there is a need to identify risk factors to inform development of effective prevention strategies. Prior research suggests adverse childhood experiences (ACEs) are common among individuals using stimulants and may be an important target for prevention. National Epidemiological Survey on Alcohol and Related Conditions was used to estimate prevalence of ACEs among U.S. adults using amphetamine-type stimulants (ATS), cocaine, or both. Multivariable logistic regression examined associations between ACEs and stimulant use and use disorders. Among adults reporting lifetime ATS use, 22.1% had ≥4 ACEs, 24.9% had 2-3 ACEs, 22.4% had 1 ACE, 30.6% reported no ACEs. Among adults with lifetime ATS use disorder, 29.3% reported ≥4 ACEs, 28.7% reported 2-3 ACEs, 21.6% reported 1 ACE, and 20.4% reported no ACEs. Multivariable logistic regression found a significant relationship between number of ACEs and stimulant use and use disorders. In conclusion, we found a strong relationship between increasing ACE exposures and stimulant use and use disorders. Advancing comprehensive strategies to prevent ACEs and treating underlying trauma among those using stimulants holds great promise to reduce stimulant use and its health and social consequences in the United States.